Bank Ownership Dynamics and Macroprudential Policy Effectiveness in Mitigating the Impact of Monetary Shocks on Asset Quality - Karona Cahya Susena; Nenden Restu Hidayah; Mujiono; Ahmad Syafran (Journal of Economics and Management, 2025)
This study explores how bank ownership affects the effectiveness of macroprudential policies in reducing the impact of monetary shocks on bank asset quality in Indonesia. The study is motivated by the idea that monetary tightening does not affect all banks equally, as ownership characteristics shape how banks respond to changes in the policy rate. Quarterly panel data from 40 Indonesian commercial banks during 2020Q1–2025Q4 are analyzed using the two-step System Generalized Method of Moments (System-GMM) to address dynamic effects, endogeneity, and differences across ownership groups. Bank asset quality is measured by the non-performing loan (NPL) ratio, while monetary shocks are proxied by changes in the Bank Indonesia policy rate. Macroprudential policy is represented through a composite index of prudential instruments, and ownership is divided into state-owned and private banks. The findings show that monetary tightening may initially improve asset quality by prompting banks to apply stricter lending standards. However, the effect weakens over time as higher borrowing costs reduce borrowers' repayment capacity and increase credit risk. The results also indicate that macroprudential policies help strengthen banking stability by containing the rise of risky credit. Furthermore, ownership structure plays an important role in policy transmission, with private banks responding more strongly to monetary policy changes than state-owned banks. These findings suggest that effective financial stability policies require stronger coordination between monetary and macroprudential measures, while accounting for differences in bank behavior driven by ownership structures.